Vbrizganje semenčice v citoplazmo človeške jajčne celice - Vlaisavljević, Veljko (Medicinski razgledi, 2001)
Treatment of a male infertility using the technique of intracytoplasmic sperm injection brought about a basis change in the possibilities of male infertility treatment. The described method of microsurgical egg fertilization makes paternity possible even in cases when only a single sperm or individual sperms are available, regardless of their origin (ejaculated or isolated from testicular tissue). The partners can expect successful treatment (pregnancy) in one ICSI attempt in 20-35%. The paper presents the indications for intracytoplasmic sperm injection application in clinical practice, the results of treatment with ICSI and findings regarding the development of children conceived with this technique. Presented are the potential risks of using the mentioned method and the findings with which we are obliged to acquaint the patients during genetic counselling.
Keywords: fertilization; Infertility, male; oploditev; zunajtelesna oploditev; Child development; neplodnost; Genetic counseling; genetics; genetika